Strategi Pembelajaran Inkuiri - Fauza Okta Ramadan; Syarif Rusdan; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The inquiry learning strategy is a learning approach that places students at the center of the learning process by emphasizing the development of critical thinking skills, analysis, and independent concept discovery through a question and answer process, exploration, and investigation. This study aims to examine the effectiveness of the inquiry learning strategy in improving students' conceptual understanding and critical thinking skills in certain subjects. The method used is quantitative research with a quasi-experimental design involving an experimental group that applies the inquiry strategy and a control group with conventional learning methods. Data were collected through conceptual understanding tests and critical thinking skills assessment instruments before and after treatment. The results of the study showed that the application of the inquiry learning strategy significantly improved students' conceptual understanding and critical thinking skills compared to conventional learning methods. In conclusion, the inquiry learning strategy is effectively used as an alternative learning method that can improve the quality of the process and student learning outcomes. The implications of this study suggest that teachers integrate inquiry strategies in learning to encourage students to become active and creative learners and improve high-level thinking skills.